Unusual structure of geranium chloroplast DNA: A triple-sized inverted repeat, extensive gene duplications, multiple inversions, and two repeat families - Palmer, Jeffrey D. (1987)
Physical and gene mapping studies reveal that chloroplast DNA from geranium (Pelargonium hortorum) has sustained a number of extensive duplications and inversions, resulting in a genome arrangement radically unlike that of other plants. At 217 kilobases in size, the circular chromosome is about 50% larger than the typical land plant chloroplast genome and is by far the largest described to date, to our knowledge. Most of this extra size can be accounted for by a 76-kilobase inverted duplication, three times larger than the normal chloroplast DNA inverted repeat. This tripling has occurred primarily by spreading of the inverted repeat into regions that are single copy in all other chloroplast genomes. Consequently, 10 protein genes that are present only once in all other land plants are duplicated in geranium. At least six inversions, occurring in both the inverted repeat and large single-copy region, must be postulated to account for all of the gene order differences that distinguish the geranium genome from other chloroplast genomes. We report the existence in geranium of two families of short dispersed repeats and hypothesize that recombination between repeats may be the major cause of inversions in geranium chloroplast DNA.